Key determinants of instructional leadership in advancing entrepreneurship education implementation in senior phase schools, North West Province, South Africa - Ngozi Blessing Enebe; Jan Heystek; Martha Matashu (Interdisciplinary Journal of Education Research)
In South Africa, the ongoing challenges of youth unemployment and poverty necessitate creative solutions, such as entrepreneurship education (EE), to bolster economic resilience. Although EE’s potential is acknowledged, its successful implementation in senior phase schools (Grades 7–9) encounters obstacles due to insufficient exploration of the factors influencing instructional leadership, especially in resource-constrained areas like the North West Province, South Africa. This research sought to pinpoint the critical elements of instructional leadership for enhancing EE implementation in these schools. A quantitative method with a cross-sectional design was used. Data were gathered through questionnaires from 51 public secondary schools, chosen via convenience sampling, within the Ngaka Modiri Molema District (N = 437 schools). Descriptive statistical analysis indicated that in-service training, parental involvement, distributed leadership, funding and partnerships with community entrepreneurs significantly impacted the advancement of EE. These results underscore the necessity of internal institutional support, such as professional development and collaborative leadership frameworks, and external stakeholder engagement to overcome implementation challenges. The study concludes that instructional leaders, including principals, department heads and teachers, need systemic capacity-building and resource allocation to promote EE effectively. The recommendations stress the importance of school governing bodies and management teams institutionalising stakeholder collaboration while policymakers should prioritise funding and training initiatives. By addressing these factors, schools can better prepare students with entrepreneurial skills, aligning educational outcomes with national economic development objectives.